Tunable plasmon-induced transparency and slow light in terahertz chipscale semiconductor plasmonic waveguides. (28th May 2020) - Zhang, Zhaojian; Yang, Junbo; He, Xin; Han, Yunxin; Huang, Jie; Chen, Dingbo
Abstract: We numerically propose plasmon-induced transparency (PIT) and the slow light effect based on a terahertz (THz) chipscale plasmonic semiconductor-insulator-semiconductor waveguide system. Via the coupling between two stub resonators, PIT is introduced due to the destructive interference, which can be theoretically described by the transmission-line method. Meanwhile, the strong dispersion within the transparent window will lead to the slow light effect. Via tuning the geometric parameters, the profile of PIT as well as group delay line can be arbitrarily tailored. Moreover, active control of both PIT and slow light can be realized by changing the ambient temperature. Especially, by integrating monolayer graphene into the structure, PIT and slow light can also be electrically modulated via applying voltage. This work provides geometrical, thermal and electrical approaches to manipulate THz transmission and group delay in the subwavelength scale, and can find potential applications as filters, sensors, modulators and active optical delay lines in THz ultracompact circuits.